2017
DOI: 10.1186/s11671-017-1845-y
|View full text |Cite
|
Sign up to set email alerts
|

Light-Curing Volumetric Shrinkage in Dimethacrylate-Based Dental Composites by Nanoindentation and PAL Study

Abstract: Light-curing volumetric shrinkage in dimethacrylate-based dental resin composites Dipol® is examined through comprehensive kinetics research employing nanoindentation measurements and nanoscale atomic-deficient study with lifetime spectroscopy of annihilating positrons. Photopolymerization kinetics determined through nanoindentation testing is shown to be described via single-exponential relaxation function with character time constants reaching respectively 15.0 and 18.7 s for nanohardness and elastic modulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…( 2) assuming C = 0.0018 Å −3 ) are gathered, respectively, for DRC affected to light-curing polymerization, subsequent dry aging and wet aging in Tables 1, 2, 3. In view of these best-fitted data with I 3 ~ 10% and τ 3 ~ 1.5-2.0 ns typical for (dimeth)acrylate DRC (Kluin et al 1992(Kluin et al , 1993, positron-electron interaction in the DRC Charisma ® can be identified as mixed positron-Ps trapping, where Ps trapping originates from Ps-decay channel in free-volume holes in "pure" polymer matrix (polymer subsystem), while positron trapping is revealed as free positron self-annihilation mainly in filler and filler-polymer subsystem (Shpotyuk et al 2017(Shpotyuk et al , 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 2) assuming C = 0.0018 Å −3 ) are gathered, respectively, for DRC affected to light-curing polymerization, subsequent dry aging and wet aging in Tables 1, 2, 3. In view of these best-fitted data with I 3 ~ 10% and τ 3 ~ 1.5-2.0 ns typical for (dimeth)acrylate DRC (Kluin et al 1992(Kluin et al , 1993, positron-electron interaction in the DRC Charisma ® can be identified as mixed positron-Ps trapping, where Ps trapping originates from Ps-decay channel in free-volume holes in "pure" polymer matrix (polymer subsystem), while positron trapping is revealed as free positron self-annihilation mainly in filler and filler-polymer subsystem (Shpotyuk et al 2017(Shpotyuk et al , 2020.…”
Section: Resultsmentioning
confidence: 99%
“…The PAL spectra of polymer-filler DRC are known to be composed of mixed positron-Ps trapping channels (Shpotyuk et al 2016(Shpotyuk et al , 2017(Shpotyuk et al , 2020. If Ps decay and positron trapping are interconnected so that no changes occur in other channels, these PAL spectra can be treated using the × 3-× 2-CDA methodology (Shpotyuk et al 2018).…”
Section: Pal Spectra Analysis Employing × 3-× 2-cdamentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of time-dependent studies, annihilation parameters show changes in the physical and chemical aging/degradation of polymers, 31 in the post curing of the epoxy resin system, 32 as well as in the discontinuous investigation of cured processes ex situ. [33][34][35] For the rst time, in our work, the in situ time evolution of microstructural shrinkage during photopolymerization was shown by PALS technique and related to parallel NIR-photorheology measurements giving output on macrostructural changes. Also, the kinetics of photopolymerization were described via the free-volume concept.…”
Section: Introductionmentioning
confidence: 90%
“…Such simplification makes it possible to resolve additional components in the generalized x2-term PAL spectrum for modified matrix (with lifetime τ int and intensity I int ), the compensating (τ n , I n ) input in the 1 st channel being found assuming a reasonable condition of full interchannel equilibrium. [33][34][35][36][37] Thereby, the parameterization of transformed Ps-e + traps in the photopolymerized DRC matrix can be performed accepting (τ n , I n ) and (τ int , I int ) as the respective 1 st and 2 nd components of the generalized x2-term PAL spectrum for some hypothetical medium obeying parameterization, with respect to formalization of a simple 2-state positron-trapping model. [4][5][6][7][8] The defectrelated τ int positron lifetime in this model reflects appearing/disappearing traps in dependence on a positive/negative sign of I n and I int intensities.…”
mentioning
confidence: 99%